Sexual orientation stereotypes and job candidate screening: why gay is (mostly) OK - Philippe Sterkens; Axana Dalle; Joey Wuyts; Ines Pauwels; Hellen Durinck; Stijn Baert (Journal of Population Economics, 2025)
To explain the conflicting findings on hiring discrimination against applicants in a same-sex marriage, we explore the perceptual drivers behind employers' evaluations. Therefore, we conduct a vignette experiment among recruiters, for which we test systematically selected stereotypes from earlier studies. We find causal evidence for distinct effects of same-sex marriage on candidate perceptions and interview probabilities. In particular, interview probabilities are positively (negatively) associated with the stereotype of women (men) married to a same-sex partner as being more (less) pleasant to work with compared to candidates in a different-sex marriage. In addition, interview chances are negatively associated with the stereotype of candidates in a same-sex marriage as being more outspoken. Furthermore, our data align well with the idea of a concentrated discrimination account, whereby a minority of employers who hold negative attitudes towards individuals in same-sex marriages are responsible for most instances of hiring discrimination.
Keywords: C38; J12; J71; 330; Sexual orientation; Signalling theory; Statistical discrimination; Taste-based discrimination; Hiring experiment